Wind Tunnel Testing for a New Experimental Model of Counter-rotating Wind Turbine. (2015) - Mitulet, Lucia-Andreea; Oprina, Gabriela; Chihaia, Rares-Andrei; Nicolaie, Sergiu; Nedelcu, Adrian; Popescu, Mihail
Abstract: The paper presents the achievements of INCDIE ICPE-CA on wind installations provided with counter-rotating turbines. There are envisaged both the development of an experimental model and the results following the testing activities, respectively. The experimental model submits a novelty technological character due to the unconventional innovative aspects. It represents a foregoing constructive version, preceding a wind turbine prototype with the rated power of 10-15 kW designed for power autonomy assurance within specific applications. The preliminary calculations, the numerical modelling of the wind rotors and the electric generator stand experiments have confirmed the energy conversion capacity for the double effect micro aggregate equal to 1 kW for a 10 m/s wind velocity.